The influence of drivers and barriers on female consumers’ in-store collaborative clothing consumption practices in an emerging market context - Taljaard-Swart, Hanri (University of Pretoria, 2024)
Dissertation (MSc (Consumer Science Clothing Management))--University of Pretoria, 2024.